Desafios e possibilidades no processo de (re)construção do Projeto Político-Pedagógico em uma escola pública - Anjos, Talita Donegá dos (Universidade Federal de São Carlos, 2026)
This master's thesis, linked to the Graduate Program in Education at the Federal University of São Carlos (UFSCar–PPGE), is part of the research line School Education: Theory and Critical Practices and the context of the LOED-UFSCar Research Group's work. The study is an instrumental case study that aims to analyze the process of (re)constructing the PPP in a municipal public school that, when faced with the demand to revise the document by the Municipal Department of Education, decided to meet the demand through a democratic process that would result in a document representative of the school. Funded by the Coordination for the Improvement of Higher Education Personnel (Capes) (88887.992415/2024–00), the research is based on a qualitative perspective, with data collected through participant observation, semi-structured interviews with managers, teachers, and staff, and analysis of the PPP-2025 draft. The data, interpreted using the content analysis proposed by Bardin (1995), comprises pre-analysis, exploration of the material, and treatment of the results with inferences by the researcher. The results point to the complexity inherent in democratic school management processes and reveal a process marked by tensions between the initial democratic intention and external bureaucratic and managerial pressures. The school implemented listening strategies (children, families, teachers, staff) and sought to build a document in a participatory manner but encountered obstacles such as teacher turnover, lack of time and space for collective work, resistance from teachers, and an overload of administrative demands. The final draft (2025) is a mixed document that incorporates elements of the democratic ideal but is predominantly guided by a bureaucratic-regulatory logic. It is concluded that, even in contexts of participatory intent, the construction of the PPP tends to be influenced by structural forces that limit school autonomy and the implementation of democratic management. The study contributes to reflection on the paths and contradictions of the collective construction of the PPP in public school.
Challenges and possibilities in the process of (re)constructing the Political-Pedagogical project in a public school
Keywords: Projeto Político-Pedagógico; Gestão democrática; Escola; Political-Pedagogical project; Democratic management; School; CIENCIAS HUMANAS::EDUCACAO; 4. Educação de Qualidade